(untitled) (Journal of Parents and Teachers, 2014)
An education that prepares young people well is the main wealth of citizens and societies. The essential commitments to improve education require that education authorities provide adequate teachers to meet the educational needs of all students, families move their children the critical importance of education and that teachers and schools have the means to adequately address the diversity of their students.